Using genetics to explore complement C5 as a druggable protein in periodontitis - Alayash, Zoheir; Baumeister, Sebastian-Edgar; Holtfreter, Birte; Kocher, Thomas; Baurecht, Hansjörg; Ehmke, Benjamin; Reckelkamm, Stefan Lars; Nolde, Michael (Frontiers in Immunology, 2024)
Aim An excessively activated or dysregulated complement system has been proven to be a vital contributor to the pathogenesis of periodontitis. It has been previously hypothesized that inhibiting the activity of complement component C5 by targeting the C5a receptor is a powerful candidate for treating periodontitis. Here, we apply the drug target instrumental variable (IV) approach to investigate the therapeutic effect of genetically proxied inhibition of C5 on periodontitis. Method In our primary analysis, we used 26 independent ‘cis’ single nucleotide polymorphisms as IVs from the vicinity of the encoding locus of C5 that are associated with plasma C5 levels. In a secondary analysis, we assess the validity of our primary findings, exploring the involvement of alternative downstream biomarkers, interleukin 17 (IL-17), interleukin 1β (IL-1β), and tumor necrosis factor (TNF). Summary statistics of plasma levels (C5, IL-17, IL-1β, and TNF) were obtained from a genome-wide association study (GWAS) of 35,559 European descent individuals. We extracted association statistics from a GWAS of 17,353 clinical periodontitis cases and 28,210 European controls. Wald ratios were combined using inverse-variance weighted meta-analysis. Results In our primary approach, inhibiting C5 reduced the risk of periodontitis (Odds ratio 0.89 per 1 standard deviation reduction in C5; 95% confidence Interval 0.80–0.98, p value=0.022). Our secondary analysis suggests an involvement of IL-17 within the potential causal pathway, but was inconclusive for other biomarkers. Conclusions The findings from our study suggest that C5 inhibition may reduce the risk of periodontitis, prioritizing C5 inhibitors as a potential adjunctive therapeutic intervention in this disease.